2011
DOI: 10.5897/ajpp11.246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Urtica dioica leaf extract on activities of nucleoside diphosphate kinase and acetyl coenzyme, a carboxylase, in normal and hyperglycemic rats

Abstract: Urtica dioica has been shown to have capability of reducing blood glucose through enhancing insulin secretion. The aim of this study was to assess in vivo and in vitro effects of aqueous and alcoholic extracts of U. dioica leaves on activities of Acetyl coenzyme A carboxylase (ACC), Nucleoside diphosphate kinase (NDPK) and insulin level and serum glucose concentration. The experimental animals were randomly distributed among 6 groups of 7 or 8 rats each. The treatment groups received 150 mg/kg of alloxan. Then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…34 Increased insulin action and increased insulin signals are other regulating factors of glucose metabolism. 35,36 Our observation regarding significant decreases in blood sugar levels in the intervention groups were similar to the findings of other studies, [37][38][39][40] reporting the efficacy of nettle administration on glycemic control. In spite of this, some studies showed no positive correlation between the use of nettle and declining of blood sugar.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…34 Increased insulin action and increased insulin signals are other regulating factors of glucose metabolism. 35,36 Our observation regarding significant decreases in blood sugar levels in the intervention groups were similar to the findings of other studies, [37][38][39][40] reporting the efficacy of nettle administration on glycemic control. In spite of this, some studies showed no positive correlation between the use of nettle and declining of blood sugar.…”
Section: Discussionsupporting
confidence: 90%
“…18,19 Animal studies have shown that nettle active compounds can increase insulin levels in natural diabetes and diabetes caused by streptozotocin. 39,43,44 Three possible mechanisms have been suggested for the blood glucose lowering effects of Nettle by Fakhraee and colleagues. 19 These suggestions include (a) enhancing glucose uptake by muscles through increasing formation of permeable pores, (b) stimulating the release of insulin from pancreatic beta cells, and (c) inhibiting the activity of alpha-amylase, a carbohydrate hydrolysis inhibitor, which ultimately leads to modulation of blood sugar in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Nettle purportedly inhibits key carbohydrate digestive enzymes, including α‐amylase and α‐glucosidase, and, accordingly, decreases the intestinal absorption of glucose (Rahimzadeh et al, ; Önal et al, ; Bnouham et al, ; Said et al, ). Nettle has insulin‐mimetic, insulin‐sensitizing, and insulin‐secretagogue properties; moreover, it forms unique glucose‐permeable pores in lipid bilayers, activates the peroxisome proliferator‐activated receptor‐γ and modulates the translocation of glucose transporter‐4 from the cytoplasm (Di Virgilio et al, (Di Virgilio et al, ) to the skeletal muscle (Domola et al, ; Rau et al, ; Farzami et al, ; Qujeq et al, ; Kadan et al, ). Furthermore, nettle can proliferate insulin‐producing β‐cells of the pancreatic islets of Langerhans and protect them from oxidative damage (Golalipour et al, ; Golalipour and Khori, ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to prepare the aqueous and ethanolic extract of the aerial parts of Urtica dioica, we used the methods as described by Qujeq et al (12,13,17).…”
Section: The Aqueous and Ethanolic Extract Of Aerial Parts Of Urtica mentioning
confidence: 99%
“…Alcoholic and aqueous extracts of UD leaf can repair pancreatic tissue in streptozotocin-induced diabetic models (12). UD leaves extracts (given parenterally) possess a hypoglycemic effect on alloxan hyperglycemic rats (13). UD affects on the liver enzymes activity (14).…”
Section: Introductionmentioning
confidence: 99%